Binding Affinity Characterization of Four Antennae-Enriched Odorant-Binding Proteins From Harmonia axyridis (Coleoptera: Coccinellidae) - Qu, Cheng; Yang, Zhao-kai; Wang, Su; Zhao, Hai-peng; Li, Feng-qi; Yang, Xin-ling; Luo, Chen (Frontiers in Physiology, 2022)
Harmonia axyridis is an important natural enemy that consumes many agricultural and forestry pests. It relies on a sensitive olfactory system to find prey and mates. Odorant-binding proteins (OBPs) as the first-step of recognizing volatiles, transport odors through sensillum lymph to odorant receptors (ORs). However, little is known about the molecular mechanisms of H. axyridis olfaction. In this study, four H. axyridis antenna specific OBP genes, HaxyOBP3, 5, 12, and 15, were bacterially expressed and the binding features of the four recombinant proteins to 40 substances were investigated using fluorescence competitive binding assays. Three-dimensional structure modeling and molecular docking analysis predicted the binding sites between HaxyOBPs and candidate volatiles. Developmental expression analyses showed that the four HaxyOBP genes displayed a variety of expression patterns at different development stages. The expression levels of HaxyOBP3 and HaxyOBP15 were higher in the adult stage than in the other developmental stages, and HaxyOBP15 was significantly transcriptionally enriched in adult stage. Ligand-binding analysis demonstrated that HaxyOBP3 and HaxyOBP12 only combined with two compounds, β-ionone and p-anisaldehyde. HaxyOBP5 protein displayed binding affinities with methyl salicylate, β-ionone, and p-anisaldehyde (Ki = 18.15, 11.71, 13.45 μM). HaxyOBP15 protein had a broad binding profile with (E)-β-farnesene, β-ionone, α-ionone, geranyl acetate, nonyl aldehyde, dihydro-β-ionone, and linalyl acetate (Ki = 4.33–31.01 μM), and hydrophobic interactions played a key role in the binding of HaxyOBP15 to these substances according to molecular docking. Taken together, HaxyOBP15 exhibited a broader ligand-binding spectrum and a higher expression in adult stage than HaxyOBP3, 5, 12, indicating HaxyOBP15 may play a greater role in binding volatiles than other three HaxyOBPs. The results will increase our understanding of the molecular mechanism of H. axyridis olfaction and may also result in new management strategies (attractants/repellents) that increase the biological control efficacy of H. axyridis.